2016
DOI: 10.2174/1874325001610010258
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Near-infrared Spectroscopy After Popliteal Block For Orthopaedic Foot Surgery

Abstract: Background:Noninvasive measurement of cutaneous tissue oxygenation using near-infrared spectroscopy (NIRS) has become common in peri-operative care. Following institution of peripheral nerve blocks, neurovascular alterations in the blocked region have been described.Objective:The primary aim of this study encompassed the assessment of the influence of a popliteal block on changes in regional oxygen saturation (SrO2), and the location of most prominent changes.Method:We conducted a prospective randomised contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Literature reviews indicate that only a few studies have evaluated the efficacy of NIRS monitoring in the induction of peripheral nerve blocks [4,12,13]. Unlike these studies, our study is the first comprehensive study using NIRS in the administration of infraclavicular nerve block, which is a type of upper extremity peripheral nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews indicate that only a few studies have evaluated the efficacy of NIRS monitoring in the induction of peripheral nerve blocks [4,12,13]. Unlike these studies, our study is the first comprehensive study using NIRS in the administration of infraclavicular nerve block, which is a type of upper extremity peripheral nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although there have been publications about the use of StO2 in evaluating peripheral nerve block success, there are few studies in the literature regarding its use to measure the success of peripheral block. 9,[15][16][17][18] In the first study, which showed that NIRS can capture the increase in local tissue perfusion occurring after the block, a 15% increase in oxygen saturation was detected in the limb that was performed block procedure after the brachial plexus blockage (interscalene, supraclavicular, infraclavicular or axillary). Significant increases in StO2 values were observed within 5 min after the completion of the block, which occurred before the patients perceived sensory and motor loss.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Although there have been publications about the use of StO 2 in evaluating peripheral nerve block success, there are few studies in the literature regarding its use to measure the success of peripheral block. [8,9,[15][16][17] In the first study, which showed that NIRS can capture the increase in local tissue perfusion occurring after the block, a 15% increase in oxygen saturation was detected in the limb that was performed block procedure after the brachial plexus blockage (interscalene, supraclavicular, infraclavicular, or axillary). Significant increases in StO 2 values were observed within 5 min after the completion of the block, which occurred before the patients perceived sensory and motor loss.…”
Section: Figurementioning
confidence: 99%